2007
DOI: 10.1021/es0621593
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Devices:  Passive Samplers for Measuring Dissolved Hydrophobic Organic Compounds in Aquatic Environments

Abstract: We demonstrate the use of polyethylene devices (PEDs) for assessing hydrophobic organic compounds (HOCs) in aquatic environments. Like semipermeable membrane devices (SPMDs) and solid-phase microextraction (SPME), PEDs passively accumulate HOCs in proportion to their freely dissolved concentrations. Polyethylene-water partition constants (K(PEW)S) were measured in the laboratory for eight polycyclic aromatic hydrocarbons (PAHs), five polychlorinated biphenyls (PCBs), and one polychlorinated dibenzop-dioxin (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
246
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(273 citation statements)
references
References 25 publications
21
246
2
Order By: Relevance
“…A water quality index (interstitial water toxicity criteria unit, IWCTU) was applied to examine the toxicity of heavy metals in pore water (Adams et al 2007):…”
Section: Toxicity Of Heavy Metals and Pahs In Pore Water To Aquatic Omentioning
confidence: 99%
“…A water quality index (interstitial water toxicity criteria unit, IWCTU) was applied to examine the toxicity of heavy metals in pore water (Adams et al 2007):…”
Section: Toxicity Of Heavy Metals and Pahs In Pore Water To Aquatic Omentioning
confidence: 99%
“…Adams et al [24] found that the partition coefficients of phenanthrene and pyrene between LDPE and freshwater were approximately 94% of those obtained with 0.1 M NaCl solution instead of freshwater, but the deviation could be corrected with the Setschenow constant [25]. Generally, the aqueous solubility of HOCs would decrease with increasing dissolved salt content, similar to the salting-out effects in liquidliquid extraction.…”
Section: Salinitymentioning
confidence: 99%
“…The reason for the shorter equilibration times can be qualitatively understood by considering that equilibrium attainment in a closed system is promoted by depletion of the water as well as by accumulation by the sampler. Phrased differently, in small water volumes a smaller amount of HOC needs to be transferred to the sampler before equilibrium is reached, resulting in a faster equilibrium attainment at a lower concentration level (Adams et al, 2007).…”
Section: Introductionmentioning
confidence: 99%